Millets have the potential to increase satiety and reduce the feeling of hunger: a systematic review - Anitha, Seetha; Upadhyay, Shweta; Kane-Potaka, Joanna (Frontiers in Sustainable Food Systems, 2024)
A systematic review was conducted to understand the satiety value of millets and their ability to lessen the feeling of hunger. Only six eligible studies had the relevant information for this analysis. These studies compared millet-based foods with refined rice, potatoes, wheat, oats, and rye and found that millets have the potential to lower the hunger index. The proposed mechanism suggests that millets’ richness in fiber is responsible for increasing gastric volume and prolonging gastric emptying time. Millet-based food stays longer in the stomach, thereby prolonging the feeling of satiety or fullness. Fiber also helps to slow down the release of glucose into the blood. Furthermore, the protein in millets increases insulin sensitivity, which also reduces the glucose response. This proposed mechanism, which increases satiety and delays the glucose response, is responsible for lowering the blood lipid profile and promoting weight loss.